Kuwait : Statistical Appendix. (IMF Staff Country Reports; Country Report, 2008)
The Statistical Appendix of Kuwait discusses the basic social and demographic indicators, selected economic indicators, GDP, balance of payments, gross domestic expenditure, LPG and oil production, disposal, and prices, consumer price index, wholesale price index, industrial output, agricultural and fisheries production, population and employment, government revenue, import and export, bank credit and interest rates, monetary accounts and monetary survey, and summary of government finance for the period 2001-07.